Broun, Bettie Lee. Bettie Lee Broun to Edwin Broun, Petersburg, VA, November 6, 1862. - Broun, Bettie Lee (Valdosta State University Archives and Special Collections, 2020., 1862)
Southern Female College November 6, 1862 My dear Pa: I received your letter a few days ago with inexpressible joy. I have not received a line from you before since I have been here and that has been five weeks since I have been here...
Letter from Bettie Lee Broun to her father Edwin Broun. Southern Female College, Petersburg, Virginia, November 6, 1862. 4 pages on two sheets of paper.
Keywords: American Civil War (1861-1865); Broun, Bettie Lee, 1846-1927; Longstreet, James, 1821-1904; Personal correspondence; Southern Female College (Petersburg, Va.); Virginia--Petersburg; Virginia--Northumberland County; Virginia; Women College Students